Are unconfined hydrogen vapor cloud explosions credible?. Issue 1 (26th May 2014) - Thomas, James Kelly; Eastwood, Craig; Goodrich, Martin
<x xml:space="preserve">Abstract</x> Owner/operators of chemical processing and petroleum refining sites often ask whether unconfined hydrogen vapor cloud explosions (VCEs) can actually occur. This question normally arises during the course of a consequence‐based facility siting study (FSS) or a quantitative risk assessment (QRA). While it is generally recognized that a hydrogen release within a process enclosure could lead to an explosion, the potential for an external hydrogen release to cause a VCE is not as widely recognized and is often questioned. This uncertainty appears to stem from the impression that a hydrogen release always ignites quickly and near the point of release such that a flammable cloud does not have time to develop prior to ignition and/or that a hydrogen release never produces a flammable cloud of any significant volume due to its positive buoyancy. Unfortunately, neither impression is correct. Hydrogen releases are actually susceptible to delayed ignition, and hydrogen releases can form significant flammable gas clouds near grade level. Unconfined hydrogen VCEs can and do occur. Furthermore, given the potential for rapid flame acceleration associated with hydrogen, the consequences of a hydrogen VCE can be severe. Consideration of such events in FSS and QRAs is, therefore, warranted. Prior accidental hydrogen VCEs are reviewed to establish that such events do occur. Selected hydrogen VCE tests are also discussed to establish the potential severity of such events. Moosemiller and Galindo [10th Global Congress on Process Safety, 2014 Annual AIChE Meeting, New Orleans, LA, March 30–April 2, 2014] reviewed the ignition characteristics of hydrogen relative to the potential for a delayed ignition, and only the conclusions from that article are presented here. Example dispersions, using both simplified dispersion and computational fluid dynamics methods, are presented to illustrate the flammable gas volumes that can be created by hydrogen release scenarios. Blast load predictions are presented to illustrate the range of loads that could result from a hydrogen VCE due to such a release. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 36–43, 2015